Famine and Infection in War-Time - Tamas, Revai (Pakistan Journal of Nutrition, 2007)
The belief that nutrition has an effect upon susceptibility and resistance to infection seems logical and reasonable. The recorded history of mankinds demonstrates repeatedly the close association between war, famine and infection. Unfortunately, however, it must be admitted that the factual evidence supporting a causal relationship between poor diets and susceptibility to infectious diseases is far from satisfactory. However, there is no doubt that malnourished soldiers in war conditions often have a low resistance to an infection once it is established. Before considering these problems a brief summary of the defenses of the body against infection is given.